After Thirty Years Of Financial Liberalization And Reforms Of The Algerian Banking System, What Impact On The Financing Of The Algerian Economy? - Kaci Chaouch Titem; Amokrane Abdellaziz (جامعة الوادي University of Eloued, 2024)
The aim of this article is to show how the financing of the Algerian economy has evolved. To this end, we have adopted a descriptive-analytical approach, based on the Bank of Algeria's annual reports and a review of the various reforms implemented as part of financial liberalization. Nevertheless, given the fragilities and distortions that characterize its economy, the results are not commensurate with the reforms undertaken, and the country is still unable to diversify its sources of financing, which remain dependent on its hydrocarbon exports and a financial system that is still fragile and not sufficiently developed to meet its financial requirements
Keywords: Financial liberalization; monetary policy; Algerian financial system; law on Money and Credit